Single-cell analysis and machine learning identify psoriasis-associated CD8+ T cells serve as biomarker for psoriasis - He, Sijia; Liu, Lyuye; Long, Xiaoyan; Ge, Man; Cai, Menghan; Zhang, Junling (Frontiers in Genetics, 2024)
Psoriasis is a chronic inflammatory skin disease, the etiology of which has not been fully elucidated, in which CD8 + T cells play an important role in the pathogenesis of psoriasis. However, there is a lack of in-depth studies on the molecular characterization of different CD8 + T cell subtypes and their role in the pathogenesis of psoriasis. This study aims to further expound the pathogenesy of psoriasis at the single-cell level and to explore new ideas for clinical diagnosis and new therapeutic targets.Our study identified a unique subpopulation of CD8 + T cells highly infiltrated in psoriasis lesions. Subsequently, we analyzed the hub genes of the psoriasis-specific CD8 + T cell subpopulation using hdWGCNA and constructed a machine-learning prediction model, which demonstrated good efficacy.The model interpretation showed the influence of each independent variable in the model decision.Finally, we deployed the machine learning model to an online website to facilitate its clinical transformation.